2019
DOI: 10.1159/000504325
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Blockchain Technology for Data-Sharing in Oncology: Results from a Systematic Literature Review

Abstract: Background: Timely sharing of electronic health records across providers, while ensuring data security and privacy, is essential for prompt care of cancer patients, as well as for the development of medical research and the enhancement of personalized medicine. Yet, it is not trivial to achieve efficient consent management, data exchange, and access-control policy enforcement, in particular, in decentralized settings, and given the gravity of the condition such as cancer. Using blockchain technology (BCT) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 30 publications
0
33
0
2
Order By: Relevance
“…Disadvantages were cost, complexity, hype, uncertainty about this technology, and patients' lack of awareness of this new technology [57]. Other studies identified 'lack of evaluation in a real-world setting', in addition to legal, social, and technological limitations among barriers of the adoption [22,58]. Another study researched the potential challenges and proposed solutions for adopting blockchain technology in biomedical/health care domains [13].…”
Section: Implementation Challenges and Barriers To Adoptionmentioning
confidence: 99%
“…Disadvantages were cost, complexity, hype, uncertainty about this technology, and patients' lack of awareness of this new technology [57]. Other studies identified 'lack of evaluation in a real-world setting', in addition to legal, social, and technological limitations among barriers of the adoption [22,58]. Another study researched the potential challenges and proposed solutions for adopting blockchain technology in biomedical/health care domains [13].…”
Section: Implementation Challenges and Barriers To Adoptionmentioning
confidence: 99%
“…Physicians and hospitals can seamlessly pass on their findings and therapies to pharmacies, therapists, and aftercare institutions. Laboratory findings can be digitally integrated before, during, and after treatment and thus quickly be made available to all relevant entities [74]. A further area of application is telemedicine.…”
Section: Blockchain In Health Information Systemsmentioning
confidence: 99%
“…The Journal of Medical Systems has a special collection of papers on blockchain, including a study of a blockchain-based privacy-preserving record linkage (PPRL) solution [96]. Other studies of blockchain include a Swiss-American systematic review of oncology applications [97], 16 in all at the time of the study, distributed among countries, unsurprisingly USA (4 studies), Switzerland (2 studies), and Germany, Iraq, Taiwan, Italy, China (1 study per country), and a proof of principle study using a novel framework, HealthChain [98].…”
Section: Privacy: Deidentification Distributed Computation Blockchainmentioning
confidence: 99%